Pendampingan Usaha Kecil dan Menengah Donat Kentang dalam Peningkatan Efisiensi, Produktivitas, dan Pendapatan - Aristio, Andre; Wijaya, Arwin; Laudry, Daniel; Tjiputra, Graciella Angelica; Kristopher, Ivan; Widjanarko, Kezia; Tan, Veranica; Marchalina, Leonis (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This activity aims to improve the efficiency and productivity of potato donut products produced by partners, as well as the income earned from selling potato donuts. The method used is product diversification, modification of the production process, addition of distribution channels, manufacturing of recording systems, IUMK registration, and manufacturing of Donatela Donuts Potato SMEs brands. Donut potatoes are not like ordinary donuts because this product is potato-based which makes the donut's texture more tender and savory. Previously the partner's production methods were still traditional, namely manually by hand which according to the team was less efficient. The considerable motivation of the team succeeded in increasing the partners' desire to modify the production process which could increase efficiency and business productivity. The achievement of this activity is to have an automatic stirring machine or mixer that is useful for increasing the efficiency and productivity of potato donut products. In addition, it also diversifies its products into the size of potato donuts. Increased efficiency and productivity are considered important for the team because they can save production time and can increase sales levels. From the modification of production processes and product diversification by partners, the monthly net income of partners increased by 10%. In addition, the team also proposed a strategy for using business cards along with business logos to partners to expand the sales market. With the use of this strategy, the number of customers of potato donuts owned by partners has also increased.